Molecular simulation of single N and double N/S doping to carbon networks and the effect of doping dispersant - Fitria Rahmawati; Agung Tri Wijayanta; Dedi Rohendi; Dyah Purwaningsih; Shota Sato; Jun Nakamura; Arikasuci Fitonna Ridassepri (Center of Biomass & Renewable Energy (CBIORE), 2026)
This research conducted a molecular simulation of single N and double N/S doping into a carbon network. The simulation aimed to explain the effect of N and N/S doping, which was investigated experimentally by our previous research, and to prove the hypothesis that N and/or S replace a normal C site within the carbon crystal structure. Experimental data agree with the simulation result, as shown by the increasing ID/IG ratio in the Raman spectrum, which indicates defect formation after doping. Meanwhile, the XRD patterns of the doped carbon are similar to those of the undoped carbon. It suggests that the dopants N and/or S diffused and replaced the C atom from its normal site in the carbon crystal structure without forming new N and/or S-based compounds. The result is consistent with different dispersants investigated in this research, i.e., deionized water and ethanol. However, ethanol provided better dispersibility than water, resulting in a modified N/S carbon material with ethanol dispersant, NSCE, with a higher electrical conductivity of 23.74 x 10-1 Scm-1 than the N/S-modified carbon with water dispersion, NSCW, i.e., 5.97 x 10-1 Scm-1. The presence of defects increases the number of sites for charge carriers to migrate within the carbon network, making it a good electrode material for an LFP battery, with an initial charging capacity of 349.94 ± 79.04 mAh/g and an initial discharge capacity of 113.41 ± 12.59 mAh/g. The results reveal N/S-doped carbon as a sustainable candidate for lithium-ion batteries and other advanced energy storage technologies.